Classic Heirs and Premature Heirs. Desired Inheritances Versus Imposed Inheritances. A Motivation Analysis of Family Entrepreneurship in Portugal - Ana Isabel COUTO (Communications of International Proceedings, 2020)
The current paper offers a reflection derived from the results of the qualitative research component in the author’s PhD thesis on Small and Medium Enterprises (SME) and entrepreneurial dynamics in Portugal over the last thirty years (Couto, 2013). Relying on a limited, but diverse body of biographical interviews with SME business owners, a typified set of entrepreneurial pathways and contexts was identified. This paper will focus on tendential entrepreneurship pathways, also known as family entrepreneurship pathways.  Contrary to initial expectations, the motivation analysis on entrepreneurial narratives allowed for the conclusion that the taking on of management roles is not a linear process. One could have assumed that these pathways, believed to follow a (family) trend, would be linear in their progression towards entrepreneur status. However, our interviews analysis allowed for the conclusion that even in trend-like pathways, linearity in transition, motivation and life choice are not necessarily unifying features in these specific entrepreneurship pathways.
Keywords: Small and Medium-Sized Enterprises (Smes); Family Entrepreneurship; Motivation Analysis.